Human resource development model in the area of social welfare: a model with a future research approach - Jamileh Karimi; Saeed Sayadi; Masoud Pourkiani; Sanjar Salajegheh; Alireza Arabpour (Shahid Beheshti University of Medical Sciences, 2022)
Background: Many managers believe that past behavioral models fail to solve problems of systemic mechanisms. The aim of this study was to present the Human resource development model in the area of social welfare with a future research approach. Methods: This study was an applied research in terms of aim, descriptive in terms of nature and exploratory in terms of approach. The statistical population of the study included 275 experts and managers of the General Directorate of Cooperatives, Labor and Social Welfare (GDCLS) of Sistan and Baluchestan Province. The sample size according to Cochran's formula was calculated at 160 people with a quantitative stratified sampling method. Data were collected using a researcher-made questionnaire consisting of 96 questions scored on a 5-point Likert scale. Confirmatory factor analysis in AMOS-18 software was used to analyze the data. Results: Factor loadings of the human resource development measurement model (path coefficients) consisted of communication skills (0.82), job knowledge and competences (0.81), decision skills (0.80), socio-cultural variable and technological factor (0.80), behavioral factors (0.77), organizational knowledge (0.70), intellectual factors (0.66) and creativity factor (0.69) had an impact on human resource development according to the future research approach. Based on the paired t-test, there was a significant difference between the current and desired statuses of human resource development components with the futures research approach (p-value< 0.001). Conclusion: Organizations should direct organizational capitals towards support human resource development. To be successful in the future, public organizations need to study issues related to the future.